File Classification Table of Metropolitan Seminary St. Aton of Badajoz: analysis of its sections and documentary series - Vivas Moreno, Agustín; González Lozano, Francisco; Pérez Ortiz, Guadalupe (Revista General de Información y Documentación, 2015)
Files seminars are great unknown in the archival world. Files seminars guard very important documentation, especially since the Council of Trent in education. The file Metropolitan Seminary San Aton of Badajoz custody documentation from the XV century. The study documentation allows us to know the entity. In this paper, we learn the history of your file to get into the comprehensive analysis of your classification scheme. The classification will allow us to meet the generating entity and receiving documents and establish lines of classification applicable to other files seminars. Establish models for other files seminars is a very important task.